INVESTIGATION OF THE EVOLUTION OF HYDROPHOBICITY AND WETTABILITY OF PAPER IN MULTI-COLOR PRINTING PROCESS - (:unkn) unknown (EDITURA ACAD ROMANE, 2019)
One of the keys to improving print quality is to experimentally characterize the paper surface, structure and printability to obtain quality control mechanisms. In multi-color prints, determining the differences in the acceptance of the next color ink by the surface of the paper or the ink film that was previously printed is important for print quality. The criteria, such as ink setting, adhesion, color, gloss and density, in the printing process, depend on the wettability and absorbency of the paper. The surface structure of the paper is the most important factor in determining the hydrophobic properties. In this study, wetting and absorption dynamics of the printed partially hydrophobized paper surface were investigated. The aim was to measure the effect of the printed ink film on the wetting (surface free energy) and liquid absorption behavior of the paper. Liquid absorption changes on printed/unprinted paper surfaces were measured by the sessile drop method, using a contact angle-measuring device. The surface energies of the papers were calculated and evaluated according to the surface contact angle of the droplet.
Keywords: paper surface; hydrophobicity; wettability; sessile drop method; printability; DROPLET; INK; ABSORPTION; QUALITY; IMPACT; WATER; FIBER